Приоритеты и ресурсы Грузии: мифы, история, перспективы - Талаквадзе, Г.; Ломсадзе, З.; Арчвадзе, И. (Економіка природокористування і сталий розвиток, 2020)
Рассмотрены вопросы, связанные с исследованием основных социально-экономических приоритетов Грузии, нынешним состоянием ресурсообеспеченности страны. Особое внимание уделено обзору природных ресурсов на примере минеральных. С целью повышения эффективности управления экономическими процессами предложено совершенствование деятельности руководящих органов путем переходa на проектную систему руководства всего хозяйственно-экономического комплекса Грузии. The article deals with issues related to the study of the main socio-economic priorities of Georgia. The brief historical review refutes the widely circulated thesis that during the Soviet period the Georgian Republic allegedly consumed much more goods than it produced; that per capita incomes were calculated astronomically. The issues of the current state of the country's resource supply were also considered. The concept of integral resources is used and it is proposed to combine a number of traditional and newly formed groups of potential opportunities over the past decades into a single category of the so-called. "Partial resources", which, along with traditional types – natural, human and material resources, allow the most complete and comprehensive characterization of the possibility of their use for solving urgent socio-economic problems of the country. Particular attention is paid to the current state of Georgia's natural resources on the example of a brief analysis of mineral resources with an emphasis, in particular, on the resources of building and facing materials.
In order to improve the efficiency of managing economic processes, it is proposed to radically improve the activities of ministries and departments of the country by switching to the so-called "Project management system" of the entire economic and economic complex of Georgia. The main feature of this system is associated with the introduction of a three-level classification of the main projects, which will be assigned National, Sectoral and Regional levels, depending on their scale and characteristic features. This will allow developing specific programs for the rational use of the natural resources, to optimize the management system at all levels of authorities, to introduce the innovative models of sustainable management, intended to significantly improve the living standards of the population of Georgia. Досліджено питання, пов’язані з основними соціально-економічними пріоритетами Грузії. Спростовано тезу про те, що в радянський період Грузинська республіка споживала значно більше благ, ніж виробляла, а доходи в перерахунку на душу населення обчислювалися астрономічними показниками. Розглянуто нинішній стан ресурсозабезпеченості країни. Використано поняття інтегральних ресурсів і запропоновано об’єднання традиційних і знов сформованих упродовж останніх десятиліть потенційних можливостей в одну категорію – так званих парціальних ресурсів, (що включають інформаційні, комунікаційні, інноваційні, історико-культурні, генетичні, геостратегічні, адаптаційні тощо) що поряд з традиційними видами – природними, людськими і матеріальними дадуть змогу найбільш повно і всебічно охарактеризувати можливість їх застосування для вирішення актуальних завдань. Особливу увагу приділено поточному стану природних ресурсів Грузії на прикладі мінеральних, зокрема будівельних та облицювальних матеріалів. З метою підвищення ефективності управління економічними процесами вказано на доцільність удосконалення діяльності керівництва країни шляхом переходу на проектну систему управління господарсько-економічним комплексом загалом. Новизну цієї системи пов’язано з трирівневою класифікацією основних проектів, яким присвоєно національні, галузеві та регіональні ранги залежно від масштабу і характерних особливостей. Обґрунтовано, що зазначене дасть змогу розробити конкретні програми раціонального використання природних ресурсів, оптимізувати систему управління на всіх рівнях влади, упровадити інноваційні моделі сталого господарювання, покликані забезпечити значне підвищення рівня життя населення Грузії.